The Evolution of Song in the Phylloscopus Leaf Warblers (Aves: Sylviidae). A Tale of Sexual Selection, Habitat Adaptation, and Morphological Constraints - Mahler, Bettina (2009)
Differences in song between species of birds are often the most reliable criteria by which to identify them. Thus, the study of the evolution of bird song provides biologists with a powerful insight into the nature of speciation processes. Both adaptive and nonadaptive explanations have been proposed to account for the evolution of song differences in birds. In this study, we put several of these hypotheses to a test in the genus Phylloscopus, a species-rich group of Old World leaf warblers in which song is used by males for mate attraction and territory defense. We found that song characteristics contained significant amounts of phylogenetic information, although they were more labile than morphological traits. Song frequency characteristics were more phylogenetically preserved than temporal or song structure traits. Changes in body size between species were correlated with changes in maximum and minimum frequencies and frequency bandwidth: small-bodied species had higher frequencies and wider bandwidths than large-bodied species. Beak shape was not found to limit overall frequency patterns. We used an ecomorphological correlate of habitat use, the tarsus/beak ratio, to test for song adaptation to specific habitat sound transmission characteristics. We found that species with larger tarsus/beak ratio, typically inhabiting broadleaf habitats and understory vegetation, had lower emphasized frequencies in their songs, as expected if songs are adapted to maximize sound transmission. However, this relationship did not held when controlling for common descent. Song complexity, a wide-ranging measurement encompassing temporal and structural sound complexity estimates, was best explained by breeding latitude. We interpret this relationship as a correlate of increased sexual selection by mate choice toward more Northern latitudes. We failed to find a significant role of character displacement in the evolution of song in this group: sympatric pairs of species did not show larger differences in song than allopatric pairs of species. To sum up, superimposing upon large haphazard selection of song themes, selective pressures for higher song elaboration in areas of high sexual selection, and correlative change in song brought about by natural selection of body size, would explain some of the diversity of songs that are found within the genus Phylloscopus.